Peran Program Pelatihan dalam Pengembangan Keterampilan Karyawan: Studi Kasus pada PT Libra Permana - Umi Lestari Duha; Hendrajaya Hendrajaya (Mahesa Research Center, 2026)
This article aims to describe the planning and implementation of training programs, analyze their role in employee skill development, and identify supporting and inhibiting factors affecting training effectiveness at PT Libra Permana, Semarang Regency. The problem focuses on the extent to which training programs enhance work competencies and support organizational performance. The study applies human resource development and competency-based training theories as its theoretical framework. Data were collected through in-depth interviews, observation, and documentation, and analyzed qualitatively. The findings indicate that training is conducted through internal and external methods with an emphasis on direct practice relevant to job tasks, contributing to improvements in technical skills, procedural understanding, and teamwork communication. However, training effectiveness is influenced by managerial support, workload, and the absence of structured evaluation mechanisms. This study concludes that training plays a positive role in developing employee competencies but requires more systematic planning and evaluation to ensure sustainable organizational impact.